The Relationship Between Parents’ Religiosity with Students’ Characters - Lutfia Kurniati (Rayah Al-Islam, 2021)
The objective of this study were to obtain empirical evidence of the relationship between parents’ religiosity with students’ character. The participants were the students of junior high school of al Islam Kartasura (SMP Al-Islam Kartasura). The students were randomly chosen from grades VII and VIII. The research method used quantitative by regression design. The research result found that there was correlation between parents’ religiosity with students’ character in junior high school of Al Islam kartasura. It can be concluded that the good parents’ religiosity relate to the good of students’ character.